Azathioprine pulse therapy in the treatment of psoriasis - Gupta, Ramji (Journal of Pakistan Association of Dermatologists, 2016)
Objective To document the efficacy and safety of azathioprine pulse therapy in the treatment of psoriasis. Â Patients and methods Thirty five patients (group A) were given azathioprine pulse therapy (APT) which consisted of azathioprine 500 mg orally on 3 consecutive days and repeated every month. In between low dose azathioprine (100mg) daily was given. The entire treatment was divided into four phases. In phase I, APT was continued till clearance of all the lesions. In phase II (phase of remission), APT was given for another 9 months. In phase III, if there was no recurrence, high dose azathioprine was stopped and patient continued only daily low dose (100mg) azathioprine for another 9 months. In phase IV low dose azathioprine was also stopped and patients were followed up for any relapse. Another 35 patients (group B) were given methotrexate 15mg weekly orally along with coal tar ointment till complete clearances of the lesions. Â Results 30 out of 35 (85.7%) patients in group A are in clinical remission without any treatment with 5 patients lost to follow-up. 30 patients who are in phase IV, 21 are in continuous remission for more than 3 years, 6 for 1-3 years while 3 for less than 1 year after all the treatment was stopped. In group B, all patients relapsed after remission period of 91.78+14.19 days. Â Conclusion Thus azathioprine` pulse therapy has shown promising result with no recurrence of lesions for 40.14+22.56 months. Â